2016
DOI: 10.1038/srep19259
|View full text |Cite
|
Sign up to set email alerts
|

Seismology-based early identification of dam-formation landquake events

Abstract: Flooding resulting from the bursting of dams formed by landquake events such as rock avalanches, landslides and debris flows can lead to serious bank erosion and inundation of populated areas near rivers. Seismic waves can be generated by landquake events which can be described as time-dependent forces (unloading/reloading cycles) acting on the Earth. In this study, we conduct inversions of long-period (LP, period ≥20 s) waveforms for the landquake force histories (LFHs) of ten events, which provide quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 28 publications
(47 reference statements)
6
55
0
Order By: Relevance
“…Based on combined inspection of the high-and low-frequency signals generated by the Askja landslide, we distinguish three phases of landslide motion: initiation, propagation and termination Chao et al, 2016).…”
Section: Dynamics Of the Landslide Sequence From High-and Low-frequenmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on combined inspection of the high-and low-frequency signals generated by the Askja landslide, we distinguish three phases of landslide motion: initiation, propagation and termination Chao et al, 2016).…”
Section: Dynamics Of the Landslide Sequence From High-and Low-frequenmentioning
confidence: 99%
“…Long-period seismic signals of landslides from stations several thousand kilometres away can be used as references for inversions (Allstadt, 2013;Ekström and Stark, 2013;Yamada et al, 2013;Hibert et al, 2015;Chao et al, 2016) or models (Brodsky et al, 2003;Favreau et al, 2010;Schneider et al, 2010;Moretti et al, 2012) to constrain the location, mass, duration, displacement, and run-out 15 trajectories of the landslide. Short-period waves, generated by the momentum exchanges within a granular landslide mass and along its boundaries, have been used to study the detachment, moving and reposing phases of landslides (Norris, 1994;Suriñach et al, 2005;Dammeier et al, 2011;Hibert et al, 2011Deparis et al, 2008;Vilajosana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive investigation of the dynamic process of landslides not only has implications for their dynamics but also is helpful for assessing and managing catastrophic disasters (Ekström & Stark, ; Petley, ). Seismic signals are generated by landslides, as the slide mass accelerates, moves along the ground, decelerates to rest (Chao et al, ; Ekström & Stark, ; Fukao, ; Kanamori & Given, ; Takei & Kumazawa, ), and thus provide a potential way to remedy deficiencies of conventional observations (e.g., Allstadt, ; Chao et al, ; Deparis et al, ; Ekström & Stark, ; Gualtieri & Ekström, , ; Hibert et al, ; Schneider et al, ; Suriñach et al, ; Yamada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in geophysics (Kanamori et 15 al., 1984;Surin ach et al, 2005;Lin et al, 2010;Ekstro m and Stark, 2013;Chao et al, 2016;Chao et al, 2017) have suggested that the mass movement of large-scale landslides may generate ground motion. If such ground motion is recorded by seismic stations, the occurrence times of large-scale landslides can be extracted from the records.…”
Section: Introductionmentioning
confidence: 99%
“…However, the arrival times of the P-and S-waves of landslide-induced ground motion could not be clearly distinguished. As a result, a locating approach proposed by and Chao et al (2016) was adopted in this study to locate the landslide-induced signals. The cross-correlation method was used to calculate the correlations between the envelope functions of the seismic signals received by 30 different seismic stations, and subsequently the seismic sources were located with the Monte Carlo method.…”
mentioning
confidence: 99%